Long-term Outcomes of Surgical Correction of Ischemic Mitral Regurgitation - V. E. Vaykin; A. B. O. Gamzaev; M. V. Ryazanov; K. M. Aminov; E. B. Shakhov; D. D. Zhiltsov; A. N. Shamatolskiy; S. A. Zhurko; S. A. Fedorov; G. V. Bolshukhin (Инновационная медицина Кубани, 2024)
Objective: To evaluate long-term outcomes of mitral valve annuloplasty using an autologous pericardial strip (“soft support ring” type) and a rigid support ring in combination with coronary artery bypass graft (CABG) in patients with ischemic mitral regurgitation.Materials and methods: We carried out retrospective and prospective analyses of the treatment outcomes in 90 patients with coronary heart disease (CHD) and ischemic mitral regurgitation. Ischemic mitral regurgitation (grade 2 or above) was an inclusion criterion for patients with CHD. Exclusion criteria were as follows: nonischemic mitral regurgitation, acute myocardial infarction, progressive angina pectoris, and repeated heart interventions. The patients were divided into 2 groups. Patients from group 1 underwent CABG with mitral regurgitation correction using a strip of glutaraldehyde-treated autologous pericardium (“soft support ring” type) according to our own method, whereas patients from group 2 underwent CABG with mitral regurgitation correction using a rigid support ring. The analysis revealed that the groups were comparable in all the studied parameters.Results: There was no statistically significant difference in the number of postoperative complications and hospital mortality between the groups. According to the analyzed data obtained at the time of discharge, all the patients had grade 0-1 mitral regurgitation, which shows a complete restoration of the mitral valve function after annuloplasty. In addition, there was a statistically significant decrease in the end-diastolic volume and an increase in ejection fraction, which is a sign of reverse left ventricular (LV) remodeling. The mean follow-up was 44±7.4 months. No deaths were reported during the follow-up. The results of the examination in the long-term period did not reveal negative dynamics in most patients compared with the findings in the early postoperative period. The LV size also did not change significantly, and the ejection fraction demonstrated an upward trend. One patient in each group had a recurrence of grade 3 mitral regurgitation.Conclusions: The immediate outcomes showed no recurrence of mitral regurgitation, a low number of intraoperative and postoperative complications, and pronounced reverse LV remodeling. We observed stable results in the long-term follow-up: only one patient in each group had a recurrence of mitral regurgitation. Reverse LV remodeling persisted throughout the follow-up. There were no significant differences between the groups in any parameter, which indicates that the developed annuloplasty method is not inferior to the traditional technique with a rigid support ring.